Adaptive support ventilation: State of the art review (2013)
Mechanical ventilation is one of the most commonly applied interventions in intensive care units. Despite its life-saving role, it can be a risky procedure for the patient if not applied appropriately. To decrease risks, new ventilator modes continue to be developed in an attempt to improve patient outcomes. Advances in ventilator modes include closed-loop systems that facilitate ventilator manipulation of variables based on measured respiratory parameters. Adaptive support ventilation (ASV) is a positive pressure mode of mechanical ventilation that is closed-loop controlled, and automatically adjust based on the patient?s requirements. In order to deliver safe and appropriate patient care, clinicians need to achieve a thorough understanding of this mode, including its effects on underlying respiratory mechanics. This article will discuss ASV while emphasizing appropriate ventilator settings, their advantages and disadvantages, their particular effects on oxygenation and ventilation, and the monitoring priorities for clinicians.